Innocent abroad : Charles Dickens's American engagements - Meckier, Jerome (University Press of Kentucky, 1990)
In 1842, Victorian England's foremost novelist visited America, naively expecting both a return to Eden and an ideal republic that would demonstrate progress as a natural law. Instead, Charles Dickens suffered a traumatic disappointment that darkened his vision of society and human nature for the remainder of his career. His second tour, in 1867-68, ostensibly more successful, proved no antidote for the first.Using new materials -- letters, diaries, and publishers' records -- Jerome Meckier enumerates the reasons for the failure of Dickens's American tours. During the first, an informal conspi.